2023
DOI: 10.3390/ijms241310879
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Theobromine and Its Metabolites in Reducing the Risk of Uric Acid Lithiasis

Abstract: Uric acid lithiasis accounts for about 10% of all types of renal lithiasis. The most common causes of uric acid lithiasis are low urinary pH, followed by high concentration of urinary uric acid, and low diuresis. Treatment of patients consists of alkalinization of urine, reducing the consumption of purine-rich foods, and administration of xanthine oxidase inhibitors, because there are no established therapeutic inhibitors of uric acid crystallization. We recently found that theobromine inhibited uric acid crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Nevertheless, theobromine also acts as an inhibitor of UA crystallization through interaction with its crystals, which leads to the UA crystals formed having a different morphology in its presence than in its absence [9]. Moreover, theobromine and some of its metabolites (methylxanthines which lacked a substituent at position 1) contribute globally to reducing the risk of UA stones [10]. In this sense, it has been shown that the consumption of cocoa-derived products, which are rich in theobromine, reduces the risk of crystallization of UA in urine [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, theobromine also acts as an inhibitor of UA crystallization through interaction with its crystals, which leads to the UA crystals formed having a different morphology in its presence than in its absence [9]. Moreover, theobromine and some of its metabolites (methylxanthines which lacked a substituent at position 1) contribute globally to reducing the risk of UA stones [10]. In this sense, it has been shown that the consumption of cocoa-derived products, which are rich in theobromine, reduces the risk of crystallization of UA in urine [11,12].…”
Section: Introductionmentioning
confidence: 99%